Quality Measurement of Online Single Submission (Oss) Information System with Mc Call Method (Case Study of Plut Kumkm) - Dewi, Lina Astika; Muniarti, Wafiah; Fadli, Sofiansyah; Fahmi, Hairul (CV. Publikasi Indonesia, 2024)
The NTB Province Micro, Small and Medium Enterprise Cooperative Integrated Business Service Center (PLUT-KUMKM) under the West Nusa Tenggara Province Small and Medium Enterprise Cooperative Service, provides comprehensive assistance to KUMKM to increase production and competitiveness. With seven service areas, PLUT- KUMKM provides effective solutions for business actors. However, in issuing a Business Identification Number (NIB) via the OSS application. The thing is, like in the Business Licensing menu, there is a business development feature. Carrying out business development cannot be completed in one activity in one feature, users must return to the new application menu to continue the business development process and make updates. And user errors often occur such as entering information or not following the correct procedures when filling out forms. The licensing system seeks to be integrated electronically, aiming to cut bureaucracy and improve public services. This research measures the quality of the OSS system for issuing nibs based on the perceptions of 100 gardatransfumi assistants, using the McCall method . A comprehensive evaluation is carried out to identify weaknesses and necessary improvements. Measuring the quality of OSS systems using McCall's theory is important for understanding product quality attributes from the perspective of users and the software itself. The research results will provide in-depth insight into the condition of the website and recommendations for improvement. With the OSS system, the government is trying to make it easier to manage business legality. The NIB issued through OSS becomes the identity of business actors for import and export activities. Through quality measurements, systems, weaknesses and improvements to the NIB issuance process can be identified thereby ensuring better service for business actors.